2022
DOI: 10.1155/2022/4139812
|View full text |Cite
|
Sign up to set email alerts
|

Inchinkoto, the Traditional Japanese Kampo Medicine, Enhances Intestinal Epithelial Barrier Function In Vitro

Abstract: Inchinkoto (ICKT), a traditional herbal medicine that is often used as a hepatoprotective drug in Japan, has pharmacological properties that include antioxidant, anti-inflammatory, and choleretic actions. Genipin is a metabolite of geniposide and the most abundant ingredient of ICKT; furthermore, it is considered to be the active substance responsible for its pharmacological properties in the liver. Drugs with such pharmacological characteristics are expected to prevent intestinal barrier dysfunction, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In addition, oral administration of a geniposide and chlorogenic acid combination ameliorated nonalcoholic steatohepatitis by modulating the gut microbiome composition and protecting the gut barrier. It was also found that the regulation of the microbiome contributed to the anti‐obstructive jaundice effect of YCHD (Yamashita et al, 2022), and the enhancement of the intestinal epithelial barrier may be closely associated with the therapeutic effect of YCHD in metabolic disorders (Nakao et al, 2022). Therefore, we hypothesized that chemical compounds found in feces might be able to modulate gut microbiota and influence the progression of liver disease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, oral administration of a geniposide and chlorogenic acid combination ameliorated nonalcoholic steatohepatitis by modulating the gut microbiome composition and protecting the gut barrier. It was also found that the regulation of the microbiome contributed to the anti‐obstructive jaundice effect of YCHD (Yamashita et al, 2022), and the enhancement of the intestinal epithelial barrier may be closely associated with the therapeutic effect of YCHD in metabolic disorders (Nakao et al, 2022). Therefore, we hypothesized that chemical compounds found in feces might be able to modulate gut microbiota and influence the progression of liver disease.…”
Section: Resultsmentioning
confidence: 99%
“…In the cell-culture experiments, noncytotoxic concentrations must be used to accurately assess the efficacy of test substances [ 11 , 12 ]. The maximum cell-exposure duration for SST in this experimental design was 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of LPS (1 mg/mL) used to induce TJ-barrier dysfunction in the present study was high compared to those used in other studies. Previously, we used LPS at a concentration of 100 μ g/mL to induce disruption of the Caco-2 cell intestinal epithelial barrier [ 11 ] and blood-brain barrier formed by the coculture of rat brain endothelial cells, pericytes, and astrocytes [ 17 ]. This may be attributed to the differences in cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations